Kebebasan, Pluralitas, Politik Dalam Pemikiran Hannah Arendt - Moh. Khoirul Fatih (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2022)
In a pluralistic community where society is divided by beliefs, social class, culture and religion, disagreements or differences of opinion always arise. Disagreements arise due to the fact that there are many different views or philosophies of life and do not match one another. Hannah Arendt is a philosopher who is very challenging for anyone who intends to study her political philosophy. This is because he did not write something that represents a systematic political philosophy, where a main argument is explained and developed in a sequential manner starting from general themes that are always associated with political philosophy, such as authority, state, power, sovereignty, government system. Specifically, Arendt initiated the theory of action. To speak of Action theory is to enter into the central space of Arendt's political thought. The common thread of action as something that is inherent in every individual lies in the representation of the vita active (active life) and the realization of the fundamental human form as contained in Arendt's book Human Condition, namely work, work, and action. According to Hannah Arendt, preventive measures to suppress conflict do not occur, namely when public spaces can be built with openness to one another or in Hannah Arendt's theory it is called the act of communication.